Starpkultūru vadība starptautiskajā biznesā - Nadeem, Mohammad Harris (Latvijas Universitāte, 2024)
This bachelor’s thesis looks into the operational strategies used by companies in Pakistan and Latvia to address cross-cultural differences. In these diverse cultural contexts, this comparative study attempts to shed further light on the elements that contribute to effective cross-cultural management. The comparative study gives the reader insights into the effectiveness of various cross-cultural management efforts while highlighting best practices and lessons learned. By providing region-specific insights and practical examples, the research contributes to the existing body of knowledge on cross-cultural management in international business.This study can assist people from all walks of life including academia, practitioners, and policymakers by expanding knowledge of cross-cultural management processes within the Pakistani and Latvian contexts. It considers the unique characteristics, opportunities, and challenges of managing cross-cultural teams in these countries and offers guidance for organizations aiming to develop successful cross-cultural management strategies. The study examines current ideas on culture, such as Trompenaars' model of national culture differences and Hofstede's cultural dimensions, to give a framework for studying cross-cultural interactions and to lay a solid theoretical foundation. The definition of cross-cultural management and an overview of its key components open the thesis. This entails looking into the core ideas of managing cultural differences, communication philosophies, and leadership philosophies that are essential for encouraging productive cooperation in global teams. The study examines survey data after doing a theoretical investigation to determine the present status of cross-cultural management techniques in Latvia and Pakistan. In addition to the quantitative insights provided, case studies provide a more qualitative and in-depth knowledge of how businesses in both nations manage cross-cultural problems. A synthesis of the data, together with recommendations and conclusions for improving cross-cultural management techniques, finishes the thesis. The thesis is seventy-two pages long and covers a wide range of topics related to cross-cultural management in the given situations.
Cross Cultural Management in International Business
Keywords: Ekonomika un uzņēmējdarbība; cross-cultural differences; managing cross-cultural teams; cross-cultural management techniques; Hofstede's cultural dimensions; leadership philosophies